PERHITUNGAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE ACTIVITY BASED COSTING PADA PT.BASIS INDAH DI MAKASSAR - Nurfaidah Nurfaidah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The purpose of this research is to know the model of Production cost calculation by using Activity based costing method. where the data collection technique used is by doing through observation, interview and documentation. to support the problems studied by the author. The analysis method used is descriptive qualitative and quantitative analysis where in this study the authors use the application of traditional systems to charge the element of production costs on the variable cost of production. From the results of research by the authors that the calculation of perunit production cost in 2016 using the traditional system in obtaining the results of the cost of production for Chipping Rp.175.901,06 for Splite Rp.172.730,90 for stone ash Rp.163.157,01 for screening Rp.141.934,95 and for the sand of Rp.101.786,63.